2016
DOI: 10.1016/j.drugalcdep.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and STI acquisition: Secondary analysis from the AWARE study

Abstract: Objectives Sexually transmitted infections (STIs) are significant public health and financial burdens in the United States. This manuscript examines the relationship between substance use and prevalent and incident STIs in HIV-negative adult patients at STI clinics. Methods A secondary analysis of Project AWARE was performed based on 5,012 patients from 9 STI clinics. STIs were assessed by laboratory assay and substance use by self-report. Patterns of substance use were assessed using latent class analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…Nevertheless, the relative frequency of using these substances established in our study is consistent with the results of prior studies in Europe and in the US, which collected information on use during the past six months (Feaster et al, 2016;Schmidt et al, 2016). One notable exception is cannabis, which was relatively more common in these studies than in ours.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, the relative frequency of using these substances established in our study is consistent with the results of prior studies in Europe and in the US, which collected information on use during the past six months (Feaster et al, 2016;Schmidt et al, 2016). One notable exception is cannabis, which was relatively more common in these studies than in ours.…”
Section: Discussionsupporting
confidence: 90%
“…The available literature suggests that patterns of drug use among MSM differ from men who report sex with women only (Feaster et al, 2016;Hunter et al, 2014;Lhomond, Saurel-Cubizolles, Michaels, & CSF Group, 2014;Wohl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the amount of drug and alcohol use before sexual intercourse and the number of sex acts under the influence of drugs and alcohol in the intervention group significantly declined compared to the control group (Tables 2 and 3). Many studies have shown that SRDs, by disrupting the power of judgment and inhibitive behaviour, lead to increasing involvement in high-risk behaviours, especially high-risk sexual behaviours [10,13,15,[37][38][39], particularly if the substance use occurs immediately before the sexual activity [11]. As a result, improving these consequences is important because this reduction can play a great role in preventing high-risk sexual intercourse, thus preventing HIV and HBV infection [40].…”
Section: Discussionmentioning
confidence: 99%
“…Being under the influence of substances can alter judgment and inhibitory behaviors, resulting in involvement in risky and impulsive behaviors, particularly RSBs such as reduced or no condom use, increased number of sexual partners, using drugs at the time of sexual encounters, sex with high-risk sexual partners, and also exchanging sex for drugs or money (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%